(3GdWgQ GdeJNdd Hjf Oejfs - (3CMeO Hf Ydj Hf GdTQjaj Hf eMeOs
(3ChdgG (B:s
(3EYde Cf GdWgQ GdPi jchf Cbd ef NeSI YTQ jhekG ZPG JNdd Hjf GdOejf , aEf cGf (B_ (3Ci GdWgQ GdeJNdd (B_ (3Cbd ef KdGKI CjGe s
(3BNQgG (B:s
(3gPg ghGeT jMd eYVdGJ gPG GdebGe LeYfGgG ef eUfaGJ GdYdeGA GdYXGe MQQg GdTjN CMeO Hf GdTjN Ydi Hf GdTjN GdTQjai Hf GdTjN eMeO GdeQcRi dSfI EMOi hKdGKjf hCda s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs